การลดของเสียในกระบวนการรีดยางของการผลิตยางรถยนต์ - สัญชัย ไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The objectives of this thesis are to defect reduction in extruding process of tire manufacturing appropriately by using Failure Mode and Effect Analysis (FMEA). This research is started from studying the process, defined the fact , collect data and find cause of defect in extruding process of tire manufacturing with brain storming technique by using Tree Diagram, Causes and Effects Diagram ,Relation Diagram and Failure Mode and Effect Analysis (FMEA). After that, specialists in tire manufacturing analyze and evaluate the Severity, Occurrence and Detection of each defect to calculate Risk Priority Number (RPN) help to specific risk of defect occurrence. The meaning for high RPN is the risk of high defect occurrence. The research improves processes which have RPN higher value than 100. The improvements are improve the Tuber machine and concerned equipments, make the standard of properly method, training, etc. The results of the improvement operation are the percent defects in extruding process from 26.07% to 14.82% (11.29% reduction) 1 Scrap component are reduced from 2.09% to 0.74% (1.35% reduction) , Processing return component are reduced from 25.08% to 11.24% (13.84% reduction) and RPN are reduced about 29% to 80% from previous RPN.